Pluto's moons named. (16th July 2013) - Showstack, Randy
Abstract : In the end, it did not matter that the name Vulcan came in first place by a landslide in a nonbinding public vote to suggest names for the fourth and fifth known moons of Pluto. Despite the independent vote conducted by the SETI Institute in Mountain View, Calif., on behalf of the team that discovered the moons, the International Astronomical Union (IAU) did not select the name for a Plutonian moon. The decision came much to the dismay of actor William Shatner (who played Captain Kirk in Star Trek ). Shatner had pushed for the name Vulcan to honor the home planet of Star Trek character Dr. Spock.